The persistent decline in unionization in Western and Eastern Germany, 1980 - 2004: what can we learn from a decomposition analysis? - Claus Schnabel; Joachim Wagner (Universität Lüneburg, Institut für Volkswirtschaftslehre, 2006)
An empirical analysis of various waves of the ALLBUS social survey shows that union density fell substantially in western Germany from 1980 to 2004 and in eastern Germany from 1992 to 2004. Such a negative trend can be observed for men and women and for different groups of the workforce. Regression estimates indicate that the probability of union membership is related to a number of personal and occupational variables such as age, public sector employment and being a blue collar worker (significant in western Germany only). A decomposition analysis shows that differences in union density over time and between eastern and western Germany to a large degree cannot be explained by differences in the characteristics of employees. Contrary to wide-spread perceptions, changes in the composition of the workforce seem to have played a minor role in the fall in union density in western and eastern Germany.
Keywords: J51; 330; Gewerkschaft; Mitgliedschaft; Gewerkschaftlicher Organisationsgrad; Alte Bundesländer; Neue Bundesländer